PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR KECAMATAN MALALAYANG KOTA MANADO - Mokoginta, Muhammad Aldino; Lengkong, florence Daicy; Rares, Joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Excellent service to the community is the most prominent issues in managing public servicestoday. His vigorous demands made by the community to the Government to implement the Organization ofgood governance in line with the increase in the level of the knowledge society, in addition to the presenceof the influence of globalization. Old patterns of organization of the Government does not comply with theorder of people's lives that have been changed. It encourages researchers to review the existing publicservices of Kecamatan Offices in Malalayang Manado city.Methods used in this research is descriptive method of analysis, with data collection through surveys andinterviews with voters question form the necessary information in this study. In this study, respondentsselected by purposive sampling. The respondents in this study is a community that takes care of Manadocity ID card, KK, birth certificate, and the certificate of the subdistrict office Moved Malalayang that addup to 80 people, with the consideration that they may represent a population research. The data analyzedin the descriptive analysis by descriptive statistics using a frequency distribution table.The results showed that: (1) the application of the principles of transparency and accountability in thepublic service in the Office of Sub-district is a low level Malalayang means not yet implemented properly;(2) the productivity of the public service in the low category, meaning that Kecamatan offices of Ministersapparatus Malalayang is less able to work in the public service in accordance with the expectations of theorganization i.e. work achieve the mission and objectives of the Organization; (3) the quality of the publicservice work in the Office of Subdistrict Malalayang in category is low, meaning that it has not been inaccordance with the expectations and desires of the community.The research gives the conclusion that the public service's Office in Manado city Malalayang Sub-districthas not been implemented as expected. For it suggested more needs to be increased transparency andaccountability of public service, public service, productivity and quality of work of public service.Keywords: Organizing, Public Service, Office Of Sub-district